Challenges faced when identifying patients for combination immunotherapy. (August 2017) - Ernstoff, Marc S; Gandhi, Shipra; Pandey, Manu; Puzanov, Igor; Grivas, Petros; Montero, Alberto; Velcheti, Vamsidhar; Turk, Mary Jo; Diaz-Montero, Claudia Marcela; Lewis, Lionel D; Morrison, Carl
In 1996, Jim Allison demonstrated that blocking the immune regulatory molecule CTLA-4 with anit-CTLA4 antibody led to enhance tumor responses in mice. It would take an additional 15 years for human studies to confirm the potency and clinical efficacy of anti-CTLA4, ultimately leading to US FDA approval of the first checkpoint inhibitor, ipilimumab. Now with a plethora of immune-modulating agents demonstrating single agent safety and benefit across many tumor types, investigation on the optimal combination of immune-based therapies has begun in earnest. While there are many challenges, a central one is how to select which combination for which patient is the best. Here we review the current approaches that a practitioner can use to achieve this therapeutic goal.